The effect of flowering stage in wheat on the infection efficiency of Ustilago tritici - Menzies, J.G.; Thomas, P.L.; Woods, S. (Phytoprotection, 1999)
In general, in western Canada, the inoculation of wheat (Triticum aestivum) lines to determine the level of resistance to Ustiiago tritici occurs when the plants are at the mid-anthesis stage of spike development. However, it is not always possible to inoculate at this stage so occasionally inoculations are done a few days before or after mid-anthesis. The objective of this study was to determine if inoculation of wheat spikes with U. tritici at different stages of spike development using the partial-vacuum method affected the number of viable seed per spike and subsequent percentage of smutted plants grown from inoculated seed. Four lines of wheat were inoculated at three different stages of spike development in the field each year for 5 years. The stages of spike development studied were preanthesis, mid-anthesis (anthers at either end of the spike were dehisced while those in the middle of the spike were yellow), and post-anthesis (all anthers dehisced). There were significant differences among the four wheat lines and the 5 years of the study for the number of viable seed per spike and the percent of smutted plants. Inoculation at post-anthesis resulted in a significantly greater number of viable seed per spike and lower percentage of smutted plants. We conclude that the partial-vacuum method of inoculation with Ustiiago tritici should be done at the pre- or midanthesis stage of wheat head development to minimize the negative effect of maturity on infection efficiency.